Digitalization in the Czech Healthcare - Klimková, Veronika (2019)
The Master’s thesis deals with the advancement of the Czech healthcare’s digitalization, firstly by providing a comprehensive sector overview and subsequently by analysing both its recent scientific results, as well as its future trends and tendencies, as seen by relevant stakeholders. In total, this gives the reader a clear understanding of which direction the Czech healthcare environment is going to assume in the period of the following 10 years. An important contribution of the thesis’ analyses is the identification of potential business opportunities.